HOspitals and patients WoRking in Unity (HOW R U?): telephone peer support to improve older patients' quality of life after emergency department discharge in Melbourne, Australia—a multicentre prospective feasibility study. Issue 6 (14th June 2018) - Lowthian, Judy A; Lennox, Alyse; Curtis, Andrea; Wilson, Gillian; Rosewarne, Cate; Smit, De Villiers; O'Brien, Debra; Browning, Colette Joy; Boyd, Lee; Smith, Cathie; Cameron, Peter; Dale, Jeremy
Abstract : Objectives: To ascertain the feasibility and acceptability of the HOW R U? programme, a novel volunteer-peer postdischarge support programme for older patients after discharge from the emergency department (ED). Design: A multicentre prospective mixed-methods feasibility study. Setting: Two tertiary hospital EDs in metropolitan Melbourne, Australia. Participants: A convenience sample of 39 discharged ED patients aged 70 years or over, with symptoms of social isolation, loneliness and/or depression. Intervention: The HOW R U? intervention comprised weekly social support telephone calls delivered by volunteer peers for 3 months following ED discharge. Primary and secondary outcome measures: The primary outcomes were feasibility of study processes, intervention acceptability to participants and retention in the programme. Secondary outcomes were changes in loneliness level (UCLA-3—3-item Loneliness Scale), mood (5-item Geriatric Depression Scale) and health-related quality of life (EQ-5D-5L and EQ-VAS) postintervention. Results: Recruitment was feasible, with 30% of eligible patients successfully recruited. Seventeen volunteer peers provided telephone support to patient participants, in addition to their usual hospital volunteer role. HOW R U? was well received, with 87% retention in the patient group, and no attrition in the volunteer group. The median age of patients was 84 years, 64% were female, and 82% lived alone. Sixty-eight per cent of patients experienced reductions in depressive symptoms, and 53% experiencing reduced feelings of loneliness, and these differences were statistically significant Patient feedback was positive and volunteers reported great satisfaction with their new role. Conclusion: HOW R U? was feasible in terms of recruitment and retention and was acceptable to both patients and volunteers. The overall results support the potential for further research in this area and provide data to support the design of a definitive trial to confirm the observed effects. Trial registration number: ANZCTRN12615000715572; Results.